Accumulation and fate processes of organochlorine pesticides (OCPs) in soil profiles in Mt. Shergyla, Tibetan Plateau: A comparison on different forest types. (September 2019) - Luo, Yadan; Yang, Ruiqiang; Li, Yingming; Wang, Pu; Zhu, Ying; Yuan, Guoli; Zhang, Qinghua; Jiang, Guibin
Abstract: Previous work documented that forest plays an important role in the deposition of persistent organic pollutants (POPs) in the southeast Tibetan Plateau (TP) due to the "forest filter effect". However, forest types in the southeast TP are entirely different and the influence on POPs fate and forest filter effect by different forests remains unclear. This study focused on the distribution and transfer of organochlorine pesticides (OCPs) in soil of different forest types (quercus, birch, fir, and spruce dominated forests) in Mt. Shergyla, southeast TP under similar environmental and meteorological conditions. Total levels of ∑HCHs, ∑DDTs and HCB in soils ranged from < LOD to 2.25 ng/g dry weight (dw), < LOD-10.2 ng/g dw, and < LOD-0.95 ng/g dw, respectively. Concentrations of OCPs in humus layers were significantly higher than those in mineral layers in the four forest types. Relatively higher ∑DDTs concentrations were found in soil profile of broadleaved birch forest, while higher concentrations of ∑HCHs and HCB were found in soil profile of coniferous fir forest, and the same trend was observed in fresh leaf samples. Air-to-ground fluxes and mobility of OCPs in the four forest types were also evaluated. Relatively higher fluxes were found in fir forests than in other forest types, suggesting that fir forest could be more effective to transfer OCPs from the air into soil in the southeast TP. The findings in this study would be helpful for improving model simulation of POPs fate in different forest ecosystem. Graphical abstract: Image 1 Highlights: Fate processes of OCPs in four dominant forest types in the Tibetan Plateau is examined. OCP concentrations in humus layer is significantly higher than in mineral layer. Higher OCP fluxes were found in fir forests than in other three forest types. The mobility of OCPs is relatively higher in broadleaved birch soil profile in Mt. Shergyla.